Penggunaan kata Allah dan Yahweh dalam Kekristenan: Mengkritisi Teologi Yahweisme - Eben Munthe; Munatar Kause; Nicolien Meggy Sumakul (Sekolah Tinggi Teologi Paulus Medan, Sumatra Utara, 2020)
The Bible is a Christian holy book and is believed to be the word of God, even though there is a lot of technical controversy with its terminology. The Bible is written in two major languages, Hebrew and Greek, besides some parts in Aramaic. In the process of becoming an Indonesian-language holy book, there are controversies that invite a lot of disputes, even some of the most correct claims. This includes the use of the word